Word-Formation : an international handbook of the languages of Europe. - Müller, Peter O., 1955-; Ohnheiser, Ingeborg; Olsen, Susan, 1948-; Rainer, Franz, 1957- (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2016)
This handbook comprises an in-depth presentation of the state of the art in word-formation. The five volumes contain 207 articles written by leading international scholars. The 16 sections of the handbook provide the reader in general articles and individual studies with a wide variety of perspectives. The final section contains 74 portraits of word-formation in the individual languages of Europe and offers an innovative perspective.